2017
DOI: 10.1111/tbj.12786
|View full text |Cite
|
Sign up to set email alerts
|

A Bio-Psychosocial Intervention Program for Improving Quality of Life in Breast Cancer Survivors - Final Outcome of a Prospective Randomized Trial

Abstract: Given the 3.1 million breast cancer survivors in America, quality of life (QoL) is a vital issue. Bio-psychosocial milieu of survivorship is increasingly important. This study assesses the impact of Bio-psychosocial Intervention (BPSI) on the QoL of breast cancer survivors utilizing Functional Assessment of Cancer Therapy - Breast (FACT-B) instrument. A prospective randomized trial was designed; intervention arm included a 4-hour BPSI coping skills class; control arm received standard of cancer and follow-up c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…19 Improvements in symptoms and QOL outcomes for survivors may be well accomplished with a comprehensive CIM approach to survivorship care. 76,77…”
Section: Resultsmentioning
confidence: 99%
“…19 Improvements in symptoms and QOL outcomes for survivors may be well accomplished with a comprehensive CIM approach to survivorship care. 76,77…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies reported on global QoL and nine studies [19][20][21][22][23][24][25][26][27] reported improved QoL in the intervention group compared to the control group. For emotional QoL, ve out of seven studies [19-21, 28, 29] reported improvement in the intervention group.…”
Section: Systematic Review Partmentioning
confidence: 99%
“…As the main force of health education implementation, nursing staff can combine the hospitals and the community to strengthen the continuity of breast cancer rehabilitation care. Psychologically, breast cancer patients should be instructed to learn the skills of psychological adjustment, because good psychosocial adaptability not only can improve their quality of life [23][24][25], but also stimulate their subjective initiative, and further encourage them to actively carry out self-management. In terms of knowledge and skills, the education and the guidance should be carried out according to the characteristics of individuals, work nature, and lifestyle to improve self-management effectiveness.…”
Section: Effect Of Self-management Abilitymentioning
confidence: 99%